Protection Coordination - An Important Task for Network Security - Jäger, Johann; Lubiatowski, Rafal; Krebs, R.; Ziegler, G. (IEEE Power & Energy Society General Meeting 2009, 2009)
This paper is dealing with the important task of protection coordination maintaining network security in nationwide power systems under changing network conditions. Existing protection systems have to be analyzed and checked under higher loading and contingency conditions. Adapted protection concepts should be evaluated applied to the network. Nowadays numerical simulation tools like PSS® SINCAL provide the possibility of a holistic simulation of network and protection behavior. This paper is presenting the results of a protection coordination study based on the proposed method. The collection of protection and network data has been done on the basis of data plausibility algorithms firstly. Numerous different network contingencies were investigated. The software assistance and the visualisation of the enormous amount of output data are described. Generic network and protection configurations leading to maloperation can be clearly found. Further on the possibility of the development of systematic solutions covering the identified practical constraints under the changing network conditions is provided. ©2009 IEEE.
UnivIS-Import:2015-04-16:Pub.2009.tech.IE.leen.protec
Keywords: Adaptive settings; Holistic simulation; Network security; Protection coordination; Protection security assessment; Systematic protection check-up

Protection Security Assessment for Large Power Systems - Jäger, Johann; Lubiatowski, Rafal; Ziegler, G.; Krebs, R. (2009 IEEE Bucharest Power Tech Conference, 2009)
Protection security assessment is an important task in nationwide power systems maintaining network security under changing network conditions. It can be reached preferably by a software assisted method of analysis which is presented in this paper. Existing protection systems have to be analyzed and checked under higher loading and contingency conditions. Adapted protection concepts should be evaluated applied to the network. Nowadays numerical simulation tools like PSS®SINCAL provide the possibility of a holistic simulation of network and protection behavior. This paper is presenting the proposed method of analysis and gives some results applying this method on a real transmission system. The collection of protection and network data has been done on the basis of data plausibility algorithms firstly. Numerous different network contingencies were investigated. The software assistance and the visualisation of the enormous amount of output data are described. Generic network and protection configurations leading to maloperation can be clearly detected. © 2009 IEEE.
UnivIS-Import:2015-04-16:Pub.2009.tech.IE.leen.protec_9
Keywords: Holistic simulation; Network security; Protection coordination; Protection security assessment; Systematic protection check-up